Biochemical and Physical Performance Responses to a Soccer Match after a 72-Hour Recovery Period - Diego Marqués-Jiménez; Julio Calleja-González; Iñaki Arratibel-Imaz; Nicolás Terrados (MDPI AG, 2022)
The physiological and neuromuscular responses at 72 h post-match are not widely researched, despite evidence showing substantial changes in recovery markers at 72 h post-match. Consequently, the aim of this study was to determine the biochemical and physical performance responses to a soccer match after a 72-h recovery period. Male soccer players of a semiprofessional team participated in this study. Before playing a friendly match, blood values of testosterone, cortisol, the testosterone-to-cortisol ratio and urea were collected and the squat jump and the Bangsbo Repeated Sprint Ability test were performed. These measurements were considered as baseline (pre match) and were obtained again after a 72-h recovery period. Results indicate that physical performance at 72 h post-match was similar to baseline (squat jump: p = 0.974; total Repeated Sprint Ability time: p = 0.381; Repeated Sprint Ability fatigue index: p = 0.864). However, perturbations in the biochemical milieu derived from the soccer match metabolic and physiological stress were still evident at this time point. While no significant differences compared to pre match were obtained in testosterone and urea concentrations after the recovery period, cortisol and testosterone-to-cortisol ratio values were significantly higher (14.74 ± 3.68 µg/dL vs. 17.83 ± 2.65 µg/dL; p = 0.045; ES 0.92 [0.00; 1.84], very likely) and lower (39.08 ± 13.26 vs. 28.29 ± 7.45; p = 0.038; ES −0.96 [−1.89; −0.04], very likely), respectively. In conclusion, soccer players have similar physical performance to the pre match after a 72-h recovery period, even with signs of biochemical and physiological stress.